New Generalizations of the Choquet Integral by Restricted Dissimilarity Functions - Lucca, Giancarlo; Asmus, Tiago; Dimuro, Graçaliz P.; Santos, Helida; Reiser, Renata S. H.; Yamin, Adenauer C.; Marco-Detchard, Cedric; Bustince, Humberto (Anais da Brazilian Conference on Intelligent Systems (BRACIS), 2025)
This paper introduces new generalizations of the Choquet integral by Restricted Dissimilarity Functions (RDFs) to construct alternative fusion operators. The Choquer-RDF-Based generalization where applied in the Fuzzy Reasoning Method (FRM) of a Fuzzy Rule-Based Classification System (FRBCS) to cope with a benchmark composed by 33 different datasets. The results indicated that this approach is an alternative to generalizations that are based in the difference operator, considered in the original functions.